Với mọi số nguyên dương $n$, để chứng minh $\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+\cdots+\dfrac{1}{(2n-1)(2n+1)}=\dfrac{n}{2n+1}$ bằng phương pháp quy nạp toán học, sau giả thiết quy nạp ta cần chứng minh điều gì?
$\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+\cdots+\dfrac{1}{(2k-1)(2k+1)}+\dfrac{1}{(2k+1)(2k+3)}=\dfrac{k+1}{2k+3}$ | |
$\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+\cdots+\dfrac{1}{(2k-1)(2k+1)}=\dfrac{k+1}{2k+3}$ | |
$\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+\cdots+\dfrac{1}{(2k-1)(2k+1)}=\dfrac{k}{2k+1}$ | |
$\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+\cdots+\dfrac{1}{(2k-1)(2k+1)}+\dfrac{1}{(2k+1)(2k+3)}=\dfrac{k}{2k+1}$ |